Field Independent/Field Dependent Student Thinking Interaction in Learning Quadratic Equations - Huda, Syaiful (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Mathematics learning occurs within the context of classroom interaction. This interaction entails the engagement of students with their peers, both within the whole class setting and within smaller group settings. Furthermore, students interact with their teachers and utilize various learning resources during the process of mathematics learning. This study aims to explore the role played by students with field-independent and field-dependent cognitive styles in the context of mathematics learning in vocational schools. The research methodology employed for this study is a case study approach. The findings of this research revealed that there existed a division of student roles within the groups, which was determined through collaborative decision-making amongst the group members. The division of student roles during class discussions can be summarized as follows: 1) In order to successfully complete the activities assigned by the teacher, it is imperative to establish a division of roles within the groups. 2) Various interaction patterns were observed, including requests for help, provision of assistance, and negotiation. 3) The pattern of Thinking Interaction observed indicated distinct roles for the three students with field-independent cognitive styles. Consequently, this finding contradicts Witkin's assertion that field independents prefer to work independently.